Possibilities of disruptive selection in dachshunds, based on earthdog trial scores - Mészöly, Tamás; Fazekas, Natasa (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2025)
Dachshunds are highly popular both historically and nowadays. They’re bred for hunting and their work is still necessary, mainly on blood tracks and in controlling red fox and badger populations. On other hand, the waste majority of these breeds are kept as family pets today, and in that role the same traits, what are essential for successful earthdog work are disadvantageous. We’ve obtained 156 earthdog trial results of 73 dogs, from eight events for modelling selection possibilities. As pedigree data of the dogs wasn’t suitable for determining it, we’ve used heritability values near h2 = 0,2 published for other populations, but to the same traits. The selection gain for hunting eagerness to the next generation would be between 4.23–4.65 scores (max. 100) with different selections pressures, while – 9.19 scores for pet purposes. In case of barking endurance future earthdogs could improve with 6,4 seconds, while dachshunds kept as companion animals could bark 8.89 s less when once started, if the population participated on trials had been a breeding stock.